On One Inequality in Approximation Theory - Leonchik, E. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We investigate one inequality in approximation theory and obtain necessary and sufficient conditions for the validity of this inequality. We present several examples demonstrating that the results obtained are unimprovable.